Pengaruh Kompensasi, Kepemimpinan, Dan Lingkungan Kerja Terhadap Kinerja Pegawai(Studi Kasus Pada Kantor Kementerian Agama Kabupaten Madiun) - Pradana, Rio Adi; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2017)
The purpose of this research is to examine the effect of compensation, leadership, and work environment to the performance of the employees at the Ministry of Religious Affairs Office in Madiun Country. Sample collection method using the technique of simple random sampling. This research is done by using the primary data. The population in this research is the employees at the Ministry of Religious Affairs Office in Madiun Country. The analysis method used is multiple regression analysis. The results that have been conducted found that compensation and work environment have a significant effect to the performance of the employees. While the leadership has no significant effect to the performance of the employees.